Assessment of Periodontal Status of Teeth with and without Single Fixed Prosthesis - Ranjit, Rebicca; Manandhar, Pratik; Bista, Soni; Subedi, Suraksha (Journal of College of Medical Sciences-Nepal, 2023)
Introduction Any dental prosthesis should be compatible with existing hard and soft tissues fulfilling the necessary functional and aesthetic requirements for the longevity of periodontal health. Hence, this study was done to assess the periodontal status of teeth rehabilitated using single fixed prosthesis and compare it with their contralateral homologue. Methods This analytical, split-mouth, cross-sectional study was conducted among patients visiting department of Periodontics, GMCTH from July 1 to February 30, 2021. The periodontal parameters (visible plaque index, gingival bleeding index, probing pocket depth, clinical attachment level) of 103 patients with single unit crown were compared with their unrestored, healthy contralateral teeth. The effect of crown material and duration of its insertion on the periodontal parameters were also assessed. The independent t-test, Mann Whitney-U test, Kruskall-Wallis test, ANOVA test were used in the study, wherever applicable. Results All periodontal parameters of crowned teeth were found to be greater in comparison to sound teeth which was statistically significant (p<0.001). The duration of crown placement did not have significant effect on periodontal health. Mean visible plaque index, probing depth and clinical attachment level were greater in all metal crown followed by metal ceramic crown and all ceramic crowns having the least values, which was statistically significant (p<0.001). Conclusions Crowned teeth had significantly larger amount of supragingival plaque, increased gingival bleeding, deeper pocket depths and greater clinical attachment loss than sound teeth. Thus, an adequate periodontal assessment and treatment, when planning a prosthodontic rehabilitation, can limit or avoid any potential detrimental effects on periodontium.